Carbon material as well as preparation method and application thereof
By pretreating and carbonizing the flame-retardant polyurethane material, carbon materials with high specific capacity and first-time Coulomb efficiency were prepared, which solved the problems of low preparation efficiency and insufficient performance in the prior art, and achieved safe and efficient preparation of carbon materials.
Patent Information
- Application Number
- CN202411905801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing carbon material preparation methods have problems such as low efficiency, low specific capacity and low first-time Coulomb efficiency, and the use of strong acids or metal-containing compounds has safety hazards and metal ion residues.
Flame-retardant polyurethane material is used as raw materials to prepare carbon materials through pretreatment and carbonization treatment. The pretreatment temperature is 300-950℃, the carbonization treatment temperature is 1000-1600℃, and the pore-forming treatment is carried out in contact with the pore-forming agent at 650-900℃.
The specific capacity of carbon materials and the efficiency of the first Coulombs are improved, and efficient preparation is achieved, while avoiding the safety hazards and metal ion residues of the use of strong acids and metal element-containing compounds.
Smart Images

Figure BDA0005204352980000121 
Figure BDA0005204352980000122 
Figure BDA0005204352980000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a carbon material and a preparation method and application thereof. Background Art
[0002] In recent years, with the vigorous development of my country's new energy industry, lithium-ion batteries and industries have become relatively mature industries. At the same time, the demand for sodium-ion batteries for large-scale energy storage related to my country's energy security is also growing. Carbon materials include carbon materials and porous carbon materials. Among them, sodium-ion batteries need to use carbon materials as negative electrodes, while lithium-ion batteries with high energy density and fast charging characteristics use porous carbon materials made of carbon materials to prepare carbon-silicon negative electrodes. Therefore, the key to the large-scale development of the battery industry lies in how to achieve the improvement of the specific capacity and the first coulomb efficiency of carbon materials and large-scale mass production.
[0003] At present, carbon materials can be prepared based on biomass precursors. Due to the differences in the morphological characteristics of different batches of biomass precursors, the prepared carbon materials have the defects of poor consistency and stability. Carbon materials with poor consistency and stability will have the defects of decreased specific capacity and first coulombic efficiency.
[0004] In order to solve the above performance problems, researchers have proposed a solution to prepare carbon materials using polymers. For example, patent CN 115535998 A prepares phenolic resin microspheres by adding phenolic resin prepolymers and catalysts to a specific solvent for gelation, and then carbonizes the microspheres to obtain phenolic resin-based spherical carbon materials. However, although the performance of the carbon material prepared by this method is greatly improved compared to the material prepared from biomass precursors, since the solid content of the phenolic resin microspheres prepared by this preparation method is only 5%-10%, this method has extremely low efficiency in preparing carbon materials and has no prospects for commercial application.
[0005] To further solve the above-mentioned preparation efficiency problem, Chinese patent CN114899520A discloses a method for preparing carbon materials by carbonizing after introducing sulfonic acid groups, phosphoric acid groups, nitro groups, carboxyl groups (partial branched oxidation products), carbon oxygen bonds (partial branched oxidation products) and other groups through activation treatment using polyvinyl chloride resin, phenolic resin or polystyrene resin as raw materials, using strong acid or compounds containing metal elements. This method has a high preparation efficiency, but when the method uses a strong acid for activation treatment, there is a defect that the strong acid is highly corrosive to the equipment and has a low safety factor; when a compound containing metal elements is used for activation treatment, although there is no risk of equipment corrosion, the method has metal ion residues, resulting in a low specific capacity and first coulomb efficiency of the obtained carbon material.
[0006] Therefore, developing a method that can achieve significant improvements in the specific capacity and first coulombic efficiency of carbon materials while ensuring high efficiency has become a research direction for those skilled in the art. Summary of the invention
[0007] The present invention provides a method for preparing a carbon material, which can achieve the technical effect of significantly improving the specific capacity and the first coulombic efficiency of the carbon material while ensuring high efficiency.
[0008] The present invention also provides a carbon material, which achieves the technical effects of high specific capacity and first coulombic efficiency.
[0009] The present invention also provides a negative electrode active material, which achieves the technical effects of high specific capacity and first coulombic efficiency.
[0010] The present invention also provides a negative electrode sheet, which achieves the technical effects of high specific capacity and first coulombic efficiency.
[0011] The present invention also provides a secondary battery, which achieves the technical effects of high specific capacity and first coulombic efficiency.
[0012] The present invention provides a method for preparing a carbon material, which comprises the process of pre-treating and carbonizing a flame retardant polyurethane material; the pre-treating temperature is 300-950°C,
[0013] The flame retardant polyurethane material contains a flame retardant, and the flame retardant contains at least one element of N, P, S, and B.
[0014] In the method for preparing the carbon material as described above, the flame retardant is selected from at least one of ammonium polyphosphate, melamine phosphinate, and triphenyl phosphate.
[0015] In the method for preparing the carbon material as described above, the flame retardant polyurethane material is a recycled flame retardant polyurethane material.
[0016] The method for preparing the carbon material as described above, wherein the heating rate of the pretreatment is 3-10°C / min, and the holding time is 1-5h; and / or,
[0017] The treatment temperature of the carbonization treatment is 1000-1600° C., and the heating rate is 1-10° C. / min.
[0018] The method for preparing the carbon material as described above, wherein the particle size of the flame retardant polyurethane material is 2-10 mm; and / or,
[0019] The product obtained by the pretreatment is crushed to a D50 of 5-15 μm, and then subjected to the carbonization treatment.
[0020] The method for preparing the carbon material as described above, further comprising the step of contacting the product obtained by the carbonization treatment with a pore-forming agent at 650-900° C. to perform pore-forming treatment;
[0021] The pore-forming agent is selected from at least one of water, carbon dioxide and alkali metal hydroxide.
[0022] The present invention also provides a carbon material, wherein the material is prepared using any one of the above-mentioned methods for preparing the carbon material.
[0023] The present invention also provides a negative electrode active material, wherein the material comprises the above-mentioned carbon material.
[0024] The present invention also provides a negative electrode sheet, wherein the negative electrode sheet comprises the above-mentioned carbon material; and / or,
[0025] Includes the above negative electrode active material.
[0026] The present invention also provides a secondary battery, the secondary battery comprising a carbon material; and / or,
[0027] comprising the above-mentioned negative electrode active material; and / or,
[0028] Including the above-mentioned negative electrode sheet.
[0029] The preparation method provided by the present invention uses a flame-retardant polyurethane material as a raw material, does not need to use additives, and can prepare a carbon material through pretreatment and carbonization treatment, thereby having a highly efficient technical effect; at the same time, during the preparation process, the flame retardant contained in the flame-retardant polyurethane material is decomposed, so that atoms of at least one element of N, P, S, and B are doped into the carbon lattice, causing changes in the charge distribution and electronic properties of the carbon structure, and inducing the generation of additional defects, so that the prepared carbon material also has the characteristics of relatively high specific capacity and first coulombic efficiency. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0031] At present, polyvinyl chloride resin, phenolic resin or polystyrene resin can be used as raw materials, and strong acid or compounds containing metal elements are used to introduce sulfonic acid group, phosphoric acid group, nitro group, carboxyl group (partial branched oxidation product), carbon oxygen bond (partial branched oxidation product) and other groups through activation treatment, and then carbonization treatment is carried out to prepare carbon materials. However, the inventors found that although the method is efficient, the carbon material obtained using the method has the defects of low specific capacity and first coulomb efficiency. According to the above phenomenon, the inventors speculate that the above defects occur because the lattice structure arrangement in the carbon material obtained by the method is defective, resulting in fewer active sites in the material that can accommodate active metal ions (such as sodium ions, lithium ions), so that the carbon material obtained by the above method has the defects of low specific capacity and first coulomb efficiency. Therefore, if a method for preparing a carbon material with a suitable crystalline structure carbon material can be developed while ensuring high efficiency, the problems existing in the above-mentioned prior art can be solved.
[0032] Based on this, the first aspect of the present invention provides a method for preparing a carbon material, which comprises sequentially pretreating and carbonizing a flame retardant polyurethane material to obtain a carbon material; the pretreatment temperature is 300-950°C.
[0033] The flame retardant polyurethane material includes a flame retardant, and the flame retardant includes at least one element of N, P, S, and B.
[0034] Polyurethane materials are widely used in the fields of construction, home appliances, etc. due to their high strength, low density, low thermal conductivity and other characteristics. Among them, flame-retardant polyurethane materials have unique safety advantages in house insulation, pipeline insulation, low-temperature transportation, etc. Flame-retardant polyurethane materials are generally prepared by adding flame retardants during the preparation process. Among them, flame retardants can be divided into additive type, reactive type and intrinsic type according to different action mechanisms.
[0035] For additive flame retardants, commonly used ones are ammonium polyphosphate (APP), expandable graphite, and melamine. The addition of N and P elements can effectively increase the limiting oxygen index (LOI) of polyurethane combustion, making the polyurethane material flame retardant.
[0036] Reactive polymerization inhibitors are a type of molecule that participates in the reaction during the polymerization process and binds to the main chain or side chain of the polymer to play a flame retardant role. They have the characteristics of low mobility and excellent long-term effectiveness, but the disadvantage is that the addition of reactive units will affect the mechanical properties of rigid foams.
[0037] The improvement strategy for intrinsic flame-retardant polyurethane is to modify the isocyanate and generate functionalized monoisocyanate by adding flame-retardant units to obtain intrinsic flame-retardant polyurethane foam.
[0038] The above-mentioned additive flame retardant, reactive flame retardant and intrinsic flame retardant all contain at least one of the doping elements (N, P, S, B). The present invention selects flame retardant polyurethane materials, especially polymers containing N and P elements as effective flame retardant components, and the heteroatom content (mass fraction wt%) can reach more than 10%.
[0039] Pretreatment of the flame retardant polyurethane material can obtain a pretreated material. The pretreatment temperature is 300-950°C. Under the pretreatment temperature, the carbon lattice is initially formed, and the doping elements contained in the flame retardant polyurethane material migrate for the first time in the carbon lattice. The pretreatment causes the doping elements to migrate to a suitable position, thereby preliminarily improving the specific capacity and the first coulombic efficiency of the obtained carbon material.
[0040] The carbonization treatment further carbonizes the pretreated material obtained by the pretreatment, and at the same time completes the secondary migration of the doping elements in the carbon lattice, so that the doping elements migrate to a suitable position, and finally obtain a carbon material. The carbonization treatment can fully carbonize the pretreated material at high temperature and at the same time migrate the doping elements in the lattice to a suitable position, so that the obtained carbon material has more active sites, so that the obtained carbon material has more prominent characteristics of higher specific capacity and first coulombic efficiency. The present invention does not limit the specific treatment conditions of the carbonization treatment, and the commonly used conditions in the field can be used.
[0041] The present invention does not limit the specific processing equipment for the carbonization treatment. In one embodiment, a roller kiln can be used for the carbonization treatment.
[0042] The inventors found that the carbon material prepared by the above method has the characteristics of high specific capacity and first coulombic efficiency. The inventors speculate that the reason may be that, first, the introduction of doping element atoms into the carbon lattice can cause changes in the charge distribution and electronic properties of the carbon structure, and induce the generation of additional defects, thereby promoting the increase of the energy storage conduction rate and specific capacity of the carbon electrode, so that the prepared carbon material has the characteristics of high specific capacity and first coulombic efficiency; secondly, the pretreatment and carbonization treatment can make the doping element atoms contained in the flame-retardant polyurethane material complete two migrations in the carbon lattice, and the prepared carbon material has more active sites, thereby improving the specific capacity and first coulombic efficiency; finally, during the pretreatment and carbonization process, the escape process of heteroatoms will affect the reconstruction of the microstructure of the carbon material, form rich metal ion binding sites, and improve the ion diffusion performance, so that the characteristics of high specific capacity and first coulombic efficiency of the carbon material are further highlighted. The above preparation method does not require activation treatment, and can be completed using sequential pretreatment and carbonization treatment, which is highly efficient. Therefore, the method for preparing the carbon material provided by the present invention has the effect of being able to prepare a carbon material with both high specific capacity and first coulombic efficiency while having high efficiency.
[0043] In order to make the carbon material prepared by the preparation method provided by the present invention have higher specific capacity and first coulombic efficiency, the flame retardant included in the flame retardant polyurethane material can be selected from at least one of ammonium polyphosphate, melamine phosphinate, and triphenyl phosphate. Since the flame retardant has a high content of N and P elements, more abundant metal ion binding sites can be formed during the pretreatment and carbonization treatment, so that the carbon material prepared by using the flame retardant polyurethane material containing the flame retardant has more prominent characteristics of higher specific capacity and first coulombic efficiency.
[0044] In order to make the preparation method of the carbon material provided by the present invention also have the advantage of low production cost, in a specific embodiment, the flame retardant polyurethane material is a recycled flame retardant polyurethane material. The recycled flame retardant polyurethane material has a low raw material price while having flame retardant properties. The price characteristics of the recycled material greatly reduce the preparation cost of the carbon material with polymer as a precursor, and have a greater competitive advantage than other precursor-based carbon materials, thereby helping to reduce the production cost of the preparation method of the carbon material provided by the present invention.
[0045] In order to further reduce the production cost of the method for preparing the carbon material provided by the present invention, in a specific embodiment, the flame retardant polyurethane material is selected from wall insulation material, pipe insulation material, and door panel filling material. The above materials contain flame retardants, can provide doping element atoms, and have a wide range of sources and low costs, which can further reduce the production cost of the method for preparing the carbon material provided by the present invention.
[0046] In order to further improve the specific capacity and first coulombic efficiency of the carbon material, in a specific embodiment, the pretreatment heating rate can be controlled to be 3-10°C / min, and the holding time can be 1-5h, wherein the holding time is the holding time after the treatment temperature is reached during the pretreatment process. The above treatment conditions can make the doping element atoms contained in the flame retardant move to a more suitable position in the carbon lattice, forming more sites that can be combined with active ions, so that the obtained carbon material has a higher specific capacity and first coulombic efficiency.
[0047] More specifically, in the above process, the treatment temperature of the carbonization treatment can be further controlled to be 1000-1600°C, and the heating rate can be 1-10°C / min. The above treatment conditions can move the doping element atoms to a more suitable position in the carbon material lattice, and the characteristics of the obtained carbon material with higher specific capacity and first coulombic efficiency are further highlighted.
[0048] In a preferred embodiment, the treatment temperature of the pretreatment can be further controlled to be 450-750°C, and the heating rate can be 3-6°C / min; further, the treatment temperature of the carbonization treatment can be controlled to be 1000-1400°C, the heating rate can be 1-3°C / min, and the treatment time can be 2-4h; in a preferred embodiment, the treatment temperature of the carbonization treatment can be controlled to be 1000-1400°C, the heating rate can be 1-10°C / min, and when the treatment temperature is reached, it can be kept warm for 2-4h. The above conditions can make the characteristics of the obtained carbon material with higher specific capacity and first coulombic efficiency more prominent.
[0049] It is understandable that in order to improve the purity of the obtained carbon material, in one embodiment, the preparation method of the carbon material provided by the present invention can select flame-retardant polyurethane rigid foam particles with a particle size of 1-20mm, preferably 2-10mm as raw materials, remove magnetic foreign matter through a magnet, and remove large particle impurities through a large-pore mesh screen; successively use detergent and clean water to wash and dry to remove inorganic impurities such as dust, and pre-treat the raw material. More specifically, the product obtained by pretreatment can also be crushed to D50 of 2-30μm, preferably 4-15μm, and then carbonized. Crushing the product obtained by pretreatment can make the treated object evenly heated during the carbonization process, and obtain a carbon material with a more uniform texture, so that the obtained carbon material has a higher specific capacity and first coulomb efficiency.
[0050] In a more specific embodiment, the method for preparing the carbon material provided by the present invention further comprises the step of contacting the product obtained by the carbonization treatment with a pore-forming agent at a temperature of 650-900° C. to perform pore-forming treatment;
[0051] The pore former is selected from at least one of water, carbon dioxide and alkali metal hydroxide.
[0052] The carbon material prepared by the above process has a high specific surface area and total pore volume, and can be used as a porous carbon material for the carbon-silicon negative electrode of lithium-ion batteries. Specifically, the specific surface area of the porous carbon material is greater than or equal to 1700 m 2 / g, total pore volume greater than or equal to 0.8cm 3 In the above process, under the reaction conditions, the pore-forming agent reacts with the product obtained by carbonization treatment to generate gas, thereby forming pores to obtain a porous carbon material.
[0053] The present invention does not limit the reaction equipment used in the above reaction. In one embodiment, the above reaction can be carried out in a fixed bed or fluidized bed reactor.
[0054] The second aspect of the present invention provides a carbon material, which is prepared using the method for preparing the carbon material provided by the first aspect of the present invention. The carbon material provided by the present invention has a specific surface area of 5-10 m2 / g and further comprises at least one doping element selected from N, P, S, and B; the mass percentage of the doping element in the carbon material is 0.15-1wt%.
[0055] The present invention does not limit the existence form of the doping elements in the carbon material, as long as at least one of the above doping elements exists in the carbon material and meets the above mass percentage range.
[0056] The inventors found that the carbon material provided by the present invention has the characteristics of high specific capacity and first coulombic efficiency. More specifically, the gram capacity of the carbon material is greater than or equal to 323 mAh / g, and the first coulombic efficiency is greater than or equal to 90%. Based on the above phenomenon, the inventors speculate that the reason may be that due to the size difference between the doping element atoms and the carbon atoms, and the electronegativity of the doping element atoms, the introduction of the doping element atoms into the carbon lattice can cause the charge distribution and electronic properties of the carbon structure to change, and induce the generation of additional defects, thereby promoting the increase of the energy storage conduction rate and specific capacity of the carbon electrode, so that the obtained carbon material has the characteristics of high specific capacity and first coulombic efficiency.
[0057] In some specific embodiments, the carbon material provided by the present invention (i.e., the product obtained by carbonization treatment) is contacted with a pore-forming agent to obtain another carbon material having a high specific surface area and total pore volume, and can be used as a porous carbon material for a carbon-silicon negative electrode of a lithium-ion battery. Specifically, the specific surface area of the porous carbon material is greater than or equal to 1700 m 2 / g, total pore volume greater than or equal to 0.8cm 3 / g.
[0058] The third aspect of the present invention provides a negative electrode active material, comprising the hard carbon material provided by the second aspect of the present invention. The negative electrode active material provided by the third aspect of the present invention can be used for the preparation of a sodium ion battery.
[0059] The fourth aspect of the present invention provides a negative electrode sheet, comprising the hard carbon material provided by the second aspect of the present invention; and / or, comprising the negative electrode active material provided by the third aspect of the present invention.
[0060] The present invention does not limit the specific preparation method of the negative electrode sheet, and the negative electrode sheet can be prepared by conventional methods in the art. In one embodiment, the negative electrode sheet can be prepared by the following method:
[0061] 1) Slurry preparation
[0062] The prepared carbon material is mixed with other ingredients into a slurry, and the usual ingredients include:
[0063] Carbon materials (active substances): the main materials that provide sodium ion storage.
[0064] Conductive agents (such as carbon black, acetylene black, Super P, single-walled carbon nanotubes, etc.) are used to enhance electronic conductivity.
[0065] Binders (such as polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR) or polyacrylic acid (PAA), etc.) are used to ensure good bonding between the electrode material and the current collector.
[0066] Stabilizers (such as carboxymethyl cellulose (CMC) etc.) are used to ensure that the slurry is dispersed stably in the solvent.
[0067] Typical proportion of slurry (mass percentage):
[0068] Carbon material: 92%
[0069] Conductive agent: 4%
[0070] Binder: 1.5%
[0071] Stabilizer: 2.5%
[0072] These materials are usually mixed with a solvent (such as N-methylpyrrolidone (NMP) or water) to a solid content of 40%, and stirred to form a uniform slurry.
[0073] 2) Coating current collector
[0074] The prepared slurry is evenly coated on the current collector (usually copper foil). The specific steps include:
[0075] Scraping: The slurry is evenly coated on the copper foil by the scraping process, and the scraper gap is controlled to make the wet film thickness of 100 microns.
[0076] Drying: Drying at a certain temperature (such as 80-120°C) to remove the solvent (such as NMP) and leave a solid hard carbon electrode material with a surface density of 3.3-3.8 mg / cm 2 .
[0077] 3) Compaction and shearing
[0078] Compacting: The dried negative electrode sheet usually needs to be rolled to increase the density and mechanical strength of the material, thereby improving the conductivity and charge-discharge performance. The compaction density of the electrode sheet is adjusted to ≥ 0.92g / cm3 by adjusting the roller gap.
[0079] Shearing: Punch the compacted pole piece into 12 mm original pieces for easy battery assembly. The fifth aspect of the present invention provides a secondary battery, which includes the carbon material provided by the second aspect of the present invention; and / or, includes the negative electrode active material provided by the third aspect of the present invention; and / or, includes the negative electrode sheet provided by the fourth aspect of the present invention. The secondary battery provided by the present invention includes a carbon material with a high first coulombic efficiency per gram capacity, and thus has the characteristics of high gram capacity and first coulombic efficiency.
[0080] The present invention does not limit the specific preparation method of the secondary battery, and it can be prepared by conventional methods in the art. In one embodiment, when the secondary battery is a sodium ion battery, it can be prepared by the following method:
[0081] Under an inert atmosphere (such as dry argon or nitrogen protection), the electrode and the diaphragm, the metal sodium sheet serving as the negative electrode, and the electrolyte (such as an ester solution containing NaPF6) are assembled into a button-type sodium-ion battery.
[0082] The carbon material and its preparation method and application provided by the present invention are further described below through specific examples:
[0083] The embodiments and comparative examples use recycled flame retardant polyurethane materials having the following characteristics:
[0084] Material A: wall insulation material, the flame retardant is ammonium polyphosphate (APP), the content is 5%wt;
[0085] Material B: Pipeline insulation material, flame retardant is melamine phosphinate (MHPA), content 2%wt;
[0086] Material C: door panel filler, flame retardant is triphenyl phosphate (TPP), content 8.5%wt;
[0087] Material D: Refrigerator insulation, no flame retardant
[0088] Material E: Pipeline insulation material, flame retardant is zinc borate (ZnB), content 5%wt
[0089] Material F: door panel filler, flame retardant new sulfur nitrogen flame retardant (SNFR), content 0.2%wt.
[0090] Example 1
[0091] This example uses material B as the raw material.
[0092] Material B was crushed into particles with a particle size of 5 mm ± 2 mm using a rotary vane crusher, washed with a 2% concentration of sodium dodecylbenzene sulfonate (SDBS) solution to remove oil and inorganic impurities, rinsed with clean water and dried.
[0093] 0.5 kg of dried material B was placed in a N2 atmosphere box furnace for pretreatment, the temperature was set to 750 ° C, the heating rate was 5 ° C / min, and the temperature was kept for 1 hour after the heating was completed to obtain a pretreated material. The weight of the pretreated material was 160 g, and the pre-carbonization mass yield was calculated to be 32%.
[0094] The pretreated material was crushed twice with a jet mill, the crushing chamber pressure was controlled at 5 barg, and the output particle size D50 was 4 μm; the crushed pre-carbonized material was transferred to a N2 atmosphere tubular furnace for carbonization treatment, the temperature was set to 1400°C, the heating rate was 3°C / min, and the temperature was kept for 1 hour after the heating was completed to obtain carbon material A1.
[0095] Example 2
[0096] The difference between this embodiment and embodiment 1 is that 0.5 kg of dried material B is replaced by 0.5 kg of dried material A, the pretreatment temperature is 950°C, the heating rate is 5°C / min, and the temperature is kept for 1 hour after the heating is completed. The pretreated material is secondary crushed by a jet mill and then carbonized. The temperature is set to 1200°C, the heating rate is 4°C / min, and the temperature is kept for 2 hours after the heating is completed.
[0097] Carbon material A2 is obtained.
[0098] Example 3
[0099] The difference between this embodiment and embodiment 1 is that 0.5 kg of dried material B is replaced by 0.5 kg of dried material C, the pretreatment temperature is 300°C, the heating rate is 3°C / min, and the temperature is kept for 5 hours after the heating is completed. The pretreated material is secondary crushed by a jet mill and then carbonized. The temperature is set to 1600°C, the heating rate is 5°C / min, and the temperature is kept for 1 hour after the heating is completed.
[0100] Carbon material A3 is obtained.
[0101] Example 4
[0102] This example uses carbon material A1 to prepare porous carbon material:
[0103] Carbon material A1 was loaded into a fixed bed reactor with an inner diameter of 50 mm, and steam preheated to 450°C was introduced at a rate of 5 g / h. The temperature of the fixed bed reaction section was 900°C. After 4 hours of reaction, the solid in the reaction tube was removed by cooling to obtain carbon material M1. The specific surface area was measured by a specific surface area tester and was 1640 m 2 / g, pore volume is 0.85m 3 / g.
[0104] Example 5
[0105] This embodiment is basically the same as embodiment 4, except that carbon material A1 is replaced by carbon material A2, the pore-forming agent is CO2, and the pore-forming temperature is 650°C to obtain carbon material M2. The specific surface area of carbon material M2 is measured by a specific surface area tester to be 1375 m 2 / g, pore volume is 0.72m 3 / g.
[0106] Example 6
[0107] The difference between this embodiment and embodiment 1 is that 0.5 kg of dried material B is replaced by 0.5 kg of dried material E, the pretreatment temperature is 500°C, the heating rate is 10°C / min, and the temperature is kept for 3 hours after the heating is completed. The pretreated material is secondary crushed by a jet mill and then carbonized. The temperature is set to 1200°C, the heating rate is 1°C / min, and the temperature is kept for 2 hours after the heating is completed.
[0108] Carbon material A4 is obtained.
[0109] Example 7
[0110] The difference between this embodiment and embodiment 1 is that 0.5 kg of dried material B is replaced by 0.5 kg of dried material F, the pretreatment temperature is 600°C, the heating rate is 7°C / min, and the temperature is kept for 2 hours after the heating is completed. The pretreated material is secondary crushed by a jet mill and then carbonized. The temperature is set to 1000°C, the heating rate is 10°C / min, and the temperature is kept for 1 hour after the heating is completed.
[0111] Carbon material A5 was obtained.
[0112] Comparative Example 1
[0113] This comparative example is substantially the same as Example 1, except that 0.5 kg of dried material A is replaced by 0.5 kg of dried material D.
[0114] Carbon material B1 was obtained.
[0115] Comparative Example 2
[0116] In this comparative example, the pretreated material obtained in Example 1 was used as carbon material B2.
[0117] Comparative Example 3
[0118] This comparative example is basically the same as Example 1, except that 0.5 kg of the dried material B is directly carbonized to obtain carbon material B3.
[0119] Test example
[0120] 1. Test of doping element content
[0121] The content of doped elements in the carbon materials obtained in each embodiment and comparative example was tested using an element analyzer; the specific surface area of the carbon materials was tested using a specific surface area tester. The results are shown in Table 1.
[0122] Table 1 Statistics of doping element content and specific surface area
[0123]
[0124] 2. Electrical performance test
[0125] Using a metallic sodium sheet as the negative electrode, the carbon material obtained in Examples 1, 2, 3, 6, 7 and Comparative Examples 1-3 as the positive electrode, and an ester electrolyte of sodium hexafluorophosphate (0.1 M) (mass ratio EC: DMC: PC = 3: 3: 4), button cells were assembled in an argon-protected glove box, and the first discharge specific capacity, reversible capacity and first coulombic efficiency of the electrochemical material were measured. The data are shown in Table 2.
[0126] The test methods for the first discharge specific capacity, reversible capacity and first coulombic efficiency are as follows: discharge at 0.1C constant current to 5mV, stand for 10 minutes, and then discharge at constant voltage to 0.01mA cutoff; after standing for 30 minutes, charge at 0.1C constant current to 1.5V cutoff. Record the first discharge and charge capacities respectively, and the percentage of charge and discharge capacity is the first coulombic efficiency.
[0127] Table 2 Electrical performance test data
[0128]
[0129]
[0130] As can be seen from Table 2, compared with the embodiments, the carbon materials prepared in the comparative examples have lower first discharge specific capacity, reversible capacity and first coulombic efficiency when applied to button cells. The reason may be that the material D used in comparative example 1 does not contain a flame retardant, and it is impossible to introduce doping element atoms into the carbon lattice to cause changes in the charge distribution and electronic properties of the carbon structure, and induce additional defects, thereby promoting the increase in the energy storage conduction rate and specific capacity of the carbon electrode; the carbon material prepared in comparative example 2 is only pretreated but not carbonized, and the carbon material prepared in comparative example 3 is directly carbonized without pretreatment, which makes it impossible for the doping element atoms contained in the flame retardant polyurethane material to complete two migrations in the carbon lattice, and thus the carbon material has fewer active sites, so the specific capacity and first coulombic efficiency are lower.
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a carbon material, characterized in that: The method comprises the steps of pre-treating and carbonizing the flame retardant polyurethane material; the pre-treating temperature is 300-950°C. The flame retardant polyurethane material contains a flame retardant, and the flame retardant contains at least one element of N, P, S, and B.
2. The method according to claim 1, characterized in that The flame retardant is selected from at least one of ammonium polyphosphate, melamine phosphinate and triphenyl phosphate.
3. The method according to claim 1 or 2, characterized in that: The flame retardant polyurethane material is a recycled flame retardant polyurethane material.
4. The method according to any one of claims 1 to 3, characterized in that The pretreatment temperature rise rate is 3-10°C / min, and the heat preservation time is 1-5h; and / or, The treatment temperature of the carbonization treatment is 1000-1600° C., and the heating rate is 1-10° C. / min.
5. The method according to any one of claims 1 to 4, characterized in that The particle size of the flame retardant polyurethane material is 2-10 mm; and / or, The product obtained by the pretreatment is crushed to a D50 of 5-15 μm, and then subjected to the carbonization treatment.
6. The method according to any one of claims 1 to 5, characterized in that The method further comprises the step of contacting the product obtained by the carbonization treatment with a pore-forming agent at 650-900° C. to perform pore-forming treatment; The pore-forming agent is selected from at least one of water, carbon dioxide and alkali metal hydroxide.
7. A carbon material, characterized in that It is prepared by the preparation method according to any one of claims 1 to 6.
8. A negative electrode active material, characterized in that: Comprising the carbon material according to claim 7.
9. A negative electrode sheet, characterized in that: Comprising the carbon material according to claim 7; and / or, comprising the negative electrode active material according to claim 8.
10. A secondary battery, characterized in that: comprising the carbon material according to claim 7; and / or, comprising the negative electrode active material according to claim 8; and / or, Including the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing hard carbon negative electrode material by utilizing recycled waste resin and application of hard carbon negative electrode material
CN114899520A
Phenolic resin-based spherical hard carbon negative electrode material with adjustable structure for sodium ion battery and preparation method of phenolic resin-based spherical hard carbon negative electrode material
CN115535998A
Porous carbon material and preparation method thereof
CN109987604A
High-temperature co-carbonization agent and application thereof to recarburizing and impurity fixing in carbonization process of plastic waste
CN110407207A
Method for recycling waste polyurethane foam and application
CN110803694A